Fiscal Policy : Issues During the Transition in Russia - Alexashenko, Sergei (Occasional Papers; Occasional Paper ;, 1998)
Since 1992, the Russian Federation has moved away from a command economy and has laid the foundation of a market-based system. This paper examines some of the key fiscal policy issues that arose in 1992-96, the period following the onset of economic liberalization and reform.